MANAGEMEN GURU PADA OTONOMI DAERAH (DESENTRALISASI) - Rozihi Rozihi; Suklani Suklani (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Continuous professional development is an important part of the teacher's education. This does not just happen, but must be planned and pursued through various opportunities. One way that teachers take is to become members of professional organizations and attend professional meetings whose agenda usually reflects the needs and interests of teachers. In this case the researchers found research results, namely: 1) Development of Teacher Management in Indonesia 2) Effective Teacher Management. The research method used is descriptive qualitative research. The results of this study have the following objectives: 1) Teacher Recruitment and Placement System. 2) Induction and Welfare Guarantee 3) Teacher Professional Development.